2016
DOI: 10.1039/c5an02554k
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo expansion of circulating lung tumor cells based on one-step microfluidics-based immunomagnetic isolation

Abstract: We describe a one-step microfludics-based immunomagnetic isolation method to isolate CTCs directly from the whole blood of lung adenocarcinoma patients. This method avoids harsh sample preparation and enrichment steps, and therefore preserves the viability of CTCs during the in vitro isolation. Importantly, isolated, magnetic bead-bearing CTCs are concentrated in a small volume of culture medium with a high CTC density. High cell viability and culturing density promote the ex vivo expansion of limited numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…After a wash (20 mL/h, 2 min) with HBSS to remove nonspecifically bound blood cells, magnets were retracted and tumor cells were released and collected in a ∼200 μL of solution. 16,17 …”
Section: Methodsmentioning
confidence: 99%
“…After a wash (20 mL/h, 2 min) with HBSS to remove nonspecifically bound blood cells, magnets were retracted and tumor cells were released and collected in a ∼200 μL of solution. 16,17 …”
Section: Methodsmentioning
confidence: 99%
“…One way to enable the molecular and functional analysis of the few CTCs that are present in circulation is to expand the CTCs ex-vivo . This has shown promise in breast, prostate and lung cancer where short term CTC culture has been performed [ 4 , 8 , 9 ]. Until recently, CTC expansion ex-vivo was the bottleneck in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, CTC expansion ex-vivo was the bottleneck in the field. The need for new isolation technologies that preserve the CTCs integrity in order to perform functional analysis has been a recent emphasis [ 9 , 10 ]. Viable CTCs grown in culture can potentially be used for therapeutic screening and used to guide patient therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Under an external magnetic field, leukocytes labelled with anti-human CD45 antibodies-coated magnetic beads were removed, and target cells left behind were effectively enriched. Wang et al [ 161 ] reported the use of a herringbone microstructure in a microfluidic MBAT chip. The introduction of a herringbone microstructure produces two favorable effects: (i) the herringbone microstructure induces vortices which bring CTCs close to herringbone grooves.…”
Section: Other Microfluidic Concentration Methodsmentioning
confidence: 99%